ARS: An Adaptive Retransmission Scheme for Contention-Based MAC Protocols in Underwater Acoustic Sensor Networks - Thi-Tham Nguyen; Seokhoon Yoon (International Journal of Distributed Sensor Networks)
Due to the limited capacity and high propagation delay of underwater communication channels, contention-based media access control (MAC) protocols suffer from a low packet delivery ratio (PDR) and a high end-to-end (E2E) delay in underwater acoustic sensor networks due to the reliance on packet retransmission for reliable data delivery. In order to address the problem of low performance, we propose a novel adaptive retransmission scheme, named ARS, which dynamically selects an optimal value of the maximum number of retransmissions, such that the successful delivery probability of a packet is maximized for a given network load. ARS can be used for various contention-based protocols and hybrid MAC protocols that have contention periods. In this paper, ARS is applied to well-known contention-based protocols, Aloha and CSMA. Simulation results show that ARS can achieve significant performance improvement in terms of PDR and E2E delay over original MAC protocols.